The impact of Industrialization of Demak Laut industrial park on the river water quality - Reena Sabrina, Binti Yusuf Latif (Universiti Malaysia Sarawak, (UNIMAS), 2008)
Increasing rapid industrialization has exerted immense pressures on water quality by introducing a large variety of chemicals into our environment. When effluents from industries are discharged into river channels, the river water is polluted physically, biologically and chemically. This study was conducted to analyze the river water quality for Temperature, pH, ~O, BOD, COD, TSS and NH3-N and to assess the extent of heavy metal pollution in the Oemak Laut Industrial Park river system) Water quality parameters such as pH. 00, Temperature, BO~, COD, TSS and NH3-N were monit6red to determine their status in relation to the health of the river ecosystem. Elemental concentrations of Zn, Cu, Hg and Pb were measured. The mean value of water quality parameters are pH, 7.6; Temperature 28.1 oC; ~O, 5.4 mglL; BOD, 4.1 mglL; COD. 45 mglL; TSS, 42.5 mgIL and NH3-N, 0.12 mglL. The highest element present in samples was Zn, 0.09 mglL in water samples and 0. 16 mglkg in sediment samples and the least abundant element was Hg, <0.001 mgIL in both samples. The levels of heavy metals did not exceed the limits designated by Interim National Water Quality Standard INWQS), World Health Organization (WHO) and Interim Sediment Quality Guidelines (ISQG). The industrial activities and other unsustainable development undertakings have occurred in the surrounding areas of the Oemak Laut Industrial Park. As a result, the impact of these activities may cause some environmental problem to the Sungai Sarawak and adjacent areas by changing the area's hydrological characteristics, which in the long terms may lead to deterioration .